The constitutional regime of the good one for living and the citizen empoderamiento - Garaicoa Ortiz, Xavier (Revista Universidad de Guayaquil, 2010)
The new regime political-constitutionalist who derives itself from the letter of Alfaro City approved by means of referendum (2008), forms a State of rights and justice, whose more sa- lient elements would be a system of rights and institutions designated like of the "good one for living" (Sumak Kawsay) sustained in the multi-nationality and interculturalidad, and, a demo- cratizante legitimador process of participativo empoderamiento of the citizenship. Unlike the legalista-administrative State of Right and the asignador social State, he himself requires a sistémica dynamics and a conception of essential justice and not only material. These would be the challenges to reach a citizenship democratically constructed in their plurality and diversity, examined in the work.